Step 1: Using Newton's second law, \( \vec{F} = m \vec{a} \), where \( m \) is the mass and \( \vec{a} \) is the acceleration.
The given velocity of the particle is:
\[
\vec{v} = (2t \hat{i} + 3t^2 \hat{j}) \, {ms}^{-1}
\]
Step 2: The acceleration is the time derivative of the velocity:
\[
\vec{a} = \frac{d\vec{v}}{dt} = \frac{d}{dt} \left( 2t \hat{i} + 3t^2 \hat{j} \right)
\]
Taking the derivative:
\[
\vec{a} = 2 \hat{i} + 6t \hat{j}
\]
Step 3: Substituting \( t = 1 \) s into the acceleration expression:
\[
\vec{a} = 2 \hat{i} + 6 \hat{j} \, {ms}^{-2}
\]
Step 4: The force \( \vec{F} \) is given as:
\[
\vec{F} = m \vec{a} = 0.5 \, {kg} \times \left( 2 \hat{i} + 6 \hat{j} \right) = 1 \hat{i} + 3 \hat{j} \, {N}
\]
Step 5: Comparing this with the given force \( \vec{F} = \left( \hat{i} + x \hat{j} \right) \, {N} \), we can see that:
\[
x = 3
\]
Thus, the value of \( x \) is 3.